2015
DOI: 10.1016/j.tjog.2014.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of maternal systemic inflammatory response in preeclampsia

Abstract: In preeclampsia, there is an increased systemic inflammatory response compared to normal pregnancy, which can influence fetal status at birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 54 publications
4
52
1
5
Order By: Relevance
“…47,48 Systemic inflammation can be rapidly activated by LPS administration in experimental models, which subsequently increases the levels of inflammatory cytokines (TNF-α or IL-1β) and oxygenfree radicals. 8,49 In the present study, we administered LPS to pregnant rats to promote the development of PE and found that the serum levels of IL-1β significantly increased in the PE group compared with the NP, NP+LPS and P groups. Furthermore, TNF-α levels also increased by 30% compared with the P group.…”
Section: The Effect Of Mgso 4 On the Pe And Seizure Modelsmentioning
confidence: 49%
See 1 more Smart Citation
“…47,48 Systemic inflammation can be rapidly activated by LPS administration in experimental models, which subsequently increases the levels of inflammatory cytokines (TNF-α or IL-1β) and oxygenfree radicals. 8,49 In the present study, we administered LPS to pregnant rats to promote the development of PE and found that the serum levels of IL-1β significantly increased in the PE group compared with the NP, NP+LPS and P groups. Furthermore, TNF-α levels also increased by 30% compared with the P group.…”
Section: The Effect Of Mgso 4 On the Pe And Seizure Modelsmentioning
confidence: 49%
“…1,8 PE has been found to involve the activation of a large number of white blood cells, 9 and inflammatory markers, such as tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6) and C-reactive protein, were increased at least twofold in PE patients compared with non-pregnant patients. [8][9][10][11][12] (TNF)-a infusion and low-dose lipopolysaccharide (LPS) infusion have been used to establish animal models of PE by inducing systemic inflammation in pregnant rats. 10 Eclampsia is associated with the development of tonic-clonic seizures in PE patients.…”
mentioning
confidence: 99%
“…Preeclampsia has been described by some as an exaggerated state of inflammation (Mihu et al 2015) and others have made the case that the endocrine profile of PE is similar to that of a non-healing wound (Bird et al 2013). In this section we will briefly review hormones of inflammation/wounding which have been described as altered in PE compared to normal pregnancy, and may have causative adverse effects on endothelial cell function.…”
Section: Hormones Of Preeclampsia-related Endothelial Dysfunctionmentioning
confidence: 99%
“…16 In addition, it is regulated by hypoxia in mature dendritic cells. 17 Preeclampsia is a disease characterized by elevated levels of proinflammatory cytokines, such as C-reactive protein, IL-6, and others [18][19][20][21] and dysregulated trophoblast differentiation. 22 Two recent studies using microarray analysis have revealed that TREM-1 is increased in preeclamptic placentas.…”
Section: Introductionmentioning
confidence: 99%